Multimorbidity in patients with acute heart failure across world regions and country income levels (REPORT-HF): a prospective, multicentre, global cohort study - Gerhardt, Teresa (2023)
Fil: Gerhardt, Teresa. Berlin Institute of Health, Berlin; Alemania